Sirtuin-3 Is Expressed by Enteric Neurons but It Does not Play a Major Role in Their Regulation of Oxidative Stress - Bubenheimer, Rebecca K.; Brown, Isola A. M.; Fried, David E.; McClain, Jonathon L.; Gulbransen, Brian D. (Frontiers in Cellular Neuroscience, 2016)
Gut inflammation contributes to the development of gut motility disorders in part by disrupting the function and survival of enteric neurons through mechanisms that involve oxidative stress. How enteric neurons regulate oxidative stress is still poorly understood. Importantly, how neuron autonomous antioxidant mechanisms contribute to the susceptibility of enteric neurons to oxidative stress in disease is not known. Here, we discover that sirtuin-3 (Sirt3), a key regulator of oxidative stress and mitochondrial metabolism, is expressed by neurons in the enteric nervous system (ENS) of the mouse colon. Given the important role of Sirt3 in the regulation of neuronal oxidative stress in the central nervous system (CNS), we hypothesized that Sirt3 plays an important role in the cell autonomous regulation of oxidative stress by enteric neurons and that a loss of Sirt3 increases neuronal vulnerability during intestinal inflammation. We tested our hypothesis using a combination of traditional immunohistochemistry, oxidative stress measurements and in vivo and ex vivo measures of GI motility in healthy and inflamed wild-type (wt) and Sirt3 null (Sirt3−/−) mice. Our results show that Sirt3 is widely expressed by neurons throughout the myenteric plexus of the mouse colon. However, the deletion of Sirt3 had surprisingly little effect on gut function and susceptibility to inflammation. Likewise, neither the genetic ablation of Sirt3 nor the inhibition of Sirt3 with antagonists had a significant effect on neuronal oxidative stress. Therefore, we conclude that Sirt3 contributes very little to the overall regulation of neuronal oxidative stress in the ENS. The functional relevance of Sirt3 in enteric neurons is still unclear but our data show that it is an unlikely candidate to explain neuronal vulnerability to oxidative stress during inflammation.